German-speaking medical students on international electives: an analysis of popular elective destinations and disciplines - Maximilian Andreas Storz; Ann-Kathrin Lederer; Eric Pieter Heymann (BMC, 2021)
Abstract Background International medical electives are a well-established part of the curriculum of many western medical schools. It is widely accepted that these electives contribute to improved clinical examination and communication skills. Overseas electives also exert a strong influence over future career decisions and often pave the way for later international work. Whilst the positive outcomes are known, little information exists regarding elective preferences and destinations overall, information that could help optimise a safe learning experience and maximise the potential for one of the highlights of medical education. In order to obtain analytical data that could assist medical elective framework development, we systematically reviewed the two largest German online databases cataloguing abroad elective testimonies. Results We identified 856 overseas elective reports uploaded within the last five years. European destinations were the most sought-after choice among German-speaking medical students. Interest in abroad electives in the United States (U.S.), a traditionally popular destination, was much lower than expected. U.S. elective reports accounted for only 3 % of long-term electives. Electives in low- and middle-income countries were generally less popular than electives in high-income countries. General surgery was the most popular elective discipline, followed by Emergency Medicine and Gynaecology and Obstetrics. Conclusions We observed a large inhomogeneity in German-speaking medical students' elective choices, potentially influenced by financial and organizational aspects as well as geopolitical developments. This highlights a crucial challenge for medical schools and other organizations involved in elective planning. In light of regional differences, our data suggest that a "one size fits all" preparation is not pertinent to optimize students' elective experience. Country- or region-specific pre-departure trainings and more individualized elective frameworks might be necessary to address these differences and to ensure a safe learning experience for students.